Preservation of immunoexpression of type I collagen, BSP and BMP4 in the dentin-pulp complex of head and neck cancer patients after radiotherapy - Jéssica Montenegro FONSÊCA; Manoela Domingues MARTINS; Pablo Agustin VARGAS; Wagner Gomes SILVA; Ana Gabriela Costa NORMANDO; Natália Rangel PALMIER; Ana Carolina Prado RIBEIRO; Thaís Bianca BRANDÃO; Márcio Ajudarte LOPES; Mário Fernando de GOES; Alan Roger SANTOS-SILVA (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract This study tested the hypothesis that head and neck radiotherapy (HNRT) impacts the immunoexpression of type I collagen, bone sialoprotein (BSP) and bone morphogenetic protein 4 (BMP4), thereby leading to micromorphological changes in the dentin-pulp complex (DPC), and promoting the onset and progression of radiation caries (RC). Twenty-two demineralized sections of carious teeth (a group of 11 irradiated teeth and a control group of 11 non-irradiated teeth) extracted from 19 head and neck cancer patients were analyzed by conventional optical microscopy and immunohistochemistry to investigate the micromorphology (cellular layer hierarchy, blood vessels, odontoblasts, fibroblasts, extracellular matrix, calcification, necrosis, reactionary dentin formation, and chronic inflammation), and the patterns of staining/immunolocalization of type I collagen, BSP and BMP4 in the dental pulp of irradiated and control samples. No significant differences attributable to the direct impact of radiotherapy were detected in DPC micromorphology between the groups. In addition, the patterns of immunohistochemical staining and immunolocalization of the proteins studied did not differ between the irradiated and the control samples for type I collagen, BSP or BMP4. This study rejected the hypothesis that HNRT directly damages dentition by changing the organic components and the microstructure of the DPC, ultimately leading to RC.